TRAINING AND MENTORING OF UMKM IN PREPARING FINANCIAL STATEMENTS USING ACCOUNTING COMPUTER APPLICATIONS - Rany Gesta Putri Rais; Nur Afni Yunita; Nurhasanah; Yunina; Mursidah; Muhammad Yusra (RADJA PUBLIKA, 2024)
Community Service activities are carried out with Donat Cici . The main objective of this community service activity is to improve the soft skills of MSME managers to compile financial reports both manually and digitally using Computer Accounting applications to facilitate business activities and decision making. The output produced in PKM activities is the expertise and ability of MSME managers to record transactions in the form of journals to compile financial reports both manually and digitally which helps the manager's business to be more efficient.